Patch-Clamp Recordings of Action Potentials From Human Atrial Myocytes: Optimization Through Dynamic Clamp - Verkerk, Arie O.; Marchal, Gerard A.; Zegers, Jan G.; Kawasaki, Makiri; Driessen, Antoine H. G.; Remme, Carol Ann; de Groot, Joris R.; Wilders, Ronald (Frontiers in Pharmacology, 2021)
Introduction: Atrial fibrillation (AF) is the most common cardiac arrhythmia. Consequently, novel therapies are being developed. Ultimately, the impact of compounds on the action potential (AP) needs to be tested in freshly isolated human atrial myocytes. However, the frequent depolarized state of these cells upon isolation seriously hampers reliable AP recordings. Purpose: We assessed whether AP recordings from single human atrial myocytes could be improved by providing these cells with a proper inward rectifier K+ current (IK1), and consequently with a regular, non-depolarized resting membrane potential (RMP), through ‘dynamic clamp’. Methods: Single myocytes were enzymatically isolated from left atrial appendage tissue obtained from patients with paroxysmal AF undergoing minimally invasive surgical ablation. APs were elicited at 1 Hz and measured using perforated patch-clamp methodology, injecting a synthetic IK1 to generate a regular RMP. The injected IK1 had strong or moderate rectification. For comparison, a regular RMP was forced through injection of a constant outward current. A wide variety of ion channel blockers was tested to assess their modulatory effects on AP characteristics. Results: Without any current injection, RMPs ranged from −9.6 to −86.2 mV in 58 cells. In depolarized cells (RMP positive to −60 mV), RMP could be set at −80 mV using IK1 or constant current injection and APs could be evoked upon stimulation. AP duration differed significantly between current injection methods (P<0.05) and was shortest with constant current injection and longest with injection of IK1 with strong rectification. With moderate rectification, AP duration at 90% repolarization (APD90) was similar to myocytes with regular non-depolarized RMP, suggesting that a synthetic IK1 with moderate rectification is the most appropriate for human atrial myocytes. Importantly, APs evoked using each injection method were still sensitive to all drugs tested (lidocaine, nifedipine, E-4031, low dose 4-aminopyridine, barium, and apamin), suggesting that the major ionic currents of the atrial cells remained functional. However, certain drug effects were quantitatively dependent on the current injection approach used. Conclusion: Injection of a synthetic IK1 with moderate rectification facilitates detailed AP measurements in human atrial myocytes. Therefore, dynamic clamp represents a promising tool for testing novel antiarrhythmic drugs.